What’s fair in child welfare?: parent knowledge, attitudes, and experiences - Cleveland, Kyndra C. (Child maltreatment, 2022)
Parents play a critical role in the progression and outcomes of juvenile dependency (child welfare court) cases. Yet, very little is known about these parents’ knowledge, attitudes, and experiences. We examined legal understanding and attitudes among 201 parents involved in ongoing dependency cases in California and Florida via semi-structured, in-person interviews. We expected parents’ understanding to be low and attitudes to be negative, particularly among parents of color and low SES parents. We expected greater dependency understanding to be related to more positive justice attitudes, and procedural and distributive justice attitudes to be indistinguishable in this population. Findings partially confirmed expectations. Parents’ understanding of the system was low, especially among parents of color and less educated parents. Parents felt less than satisfied about the fairness of procedures and decisions. However, procedural and distributive justice attitudes were distinguishable. Finally, and unexpectedly, parents’ knowledge and attitudes were negatively related. The consistently low levels of knowledge across CA and FL suggest the critical need to increase parental knowledge. It is also important to promote fair court procedures and decision-making to improve parents’ attitudes about procedural and distributive justice, which were found to be distinct and important factors among parents navigating juvenile dependency cases.